2020
DOI: 10.3389/fimmu.2020.00409
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Attenuates Acute Lung Injury Through NET Inhibition

Abstract: Introduction: Aerobic exercise improves lung inflammation in acute lung injury (ALI), but its mechanism remains unknown. Neutrophil extracellular traps (NETs) play an important role in LPS-induced ALI, and a positive correlation exists between NET formation and proinflammatory macrophage polarization. This study investigated whether aerobic exercise reduces the pro-inflammatory polarization of alveolar macrophages (AMs) by inhibiting the excessive release of NETs and then alleviating the inflammatory response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…Also, increasing the aerobic capacity can produce a preventive and curable role against respiratory infections and disorders. It can prevent or treat both pneumonia [28e30] and acute respiratory distress syndrome (ARDS) [11,31,32], which are the common disorders develop with COVID-19 and lead to a respiratory system failure. The effect of increasing the aerobic capacity on improving lung functions and preventing lung damage can be summarized into four mechanisms.…”
Section: And 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, increasing the aerobic capacity can produce a preventive and curable role against respiratory infections and disorders. It can prevent or treat both pneumonia [28e30] and acute respiratory distress syndrome (ARDS) [11,31,32], which are the common disorders develop with COVID-19 and lead to a respiratory system failure. The effect of increasing the aerobic capacity on improving lung functions and preventing lung damage can be summarized into four mechanisms.…”
Section: And 2)mentioning
confidence: 99%
“…Vieira et al [91] have reported that increasing the aerobic capacity increases levels of IL-10, which is an essential element in immunity against acute lung inflammations and injuries. A very recent study conducted by Shi et al [32] has shown that 5-weeks of mild aerobic exercises can prevent acute lung injury in mice by producing neutrophil extracellular traps (NETs) inhibition, which plays a vital role in acute lung injury. NETs are secreted by stimulated neutrophils and consist mainly of histones, DNA, myeloperoxidase, and neutrophil elastase (NE).…”
Section: The Effects Of Increasing the Aerobic Capacity On Improving mentioning
confidence: 99%
“…In that sense, it has been argued that continuing physical activity during confinement to stay healthy and maintain immune system function is a reasonable health rationale [ 7 ], as confinement generates serious problems in the physical and nutritional state of patients [ 8 ]. Indeed, exercise can play an essential role against respiratory infections and disorders, such as pneumonia and acute respiratory distress syndrome (ARDS), which are two common disorders with COVID-19 [ 9 , 10 ] and, in people in the lockdown period, it is strongly recommended to decrease the risk factors of COVID-19, improving immune and respiratory systems’ function to allow better body response against the disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to THP‐1 cells, the NF‐κB and MAPK phosphorylation levels in LPS‐stimulated peritoneal macrophages and RAW 264.7 macrophages infected with S. aureus also increased [20,21]. Alveolar macrophages isolated from LPS‐treated mice also showed a higher ratio of phosphorus‐NF‐kB/ NF‐kB that confirmed the relation between TLR‐2/4 and MAPK/ NF‐kB phosphorylation [22]. Previous studies have shown that TLR activation can regulate COX‐1 and COX‐2 through the MyD88‐dependent NF‐κB pathway, and cause changes in vasoactive factors such as Prostaglandin (PG) [23].…”
Section: Discussionmentioning
confidence: 89%